Analysis of Psychological and Organizational Factors in the Implementation of Electronic Medical Records by Medical Records Staff at Welas Asih Regional Hospital - Alfarizi, Fikri Ainta; Setiatin, Sali (Jurnal Kesmas Prima Indonesia, 2026)
This study aims to analyze the psychological and organizational factors that influence the implementation of Electronic Medical Records (EMR) by medical records staff at Welas Asih Regional Hospital. This research method uses a descriptive qualitative method in the Medical Records installation of Welas Asih Regional Hospital. A sample of 33 people was taken using a purposive sampling technique, namely officers who actively use the EMR system. Data were collected using questionnaires, observation, and documentation. Although the implementation of EMR aims to improve efficiency and quality of service, challenges that arise are changes in work culture and psychological factors such as initial anxiety. From the organizational side, the main challenges are the need for additional training and constraints on infrastructure/system smoothness. Quantitative results show that psychological factors in the form of internal motivation are at a very strong level (average score of 4.87), in line with the high awareness of officers regarding the benefits of EMR (average score of 4.67). However, aspects of initial anxiety were still identified (average score of 2.90). Organizationally, there was a strong indication of the need for additional training (average 4.41) and the persistence of technical operational barriers (average 3.31), indicating the need to optimize facility support. Optimizing RME adoption requires a holistic strategy, including the provision of psychological support programs to mitigate anxiety, as well as targeted organizational investments in improving the quality of practical training and maintaining a smoother and more stable system infrastructure.